« Identification dialectique » et genèse du patriarcat - Salima Naït Ahmed (Recherches Germaniques)
The discovery of Sohn-Rethel’s theory of knowledge in 1936 caused Adorno a “great mental shock”. But Adorno’s enthusiasm quickly gave way to Horkheimer’s rejection, as he accused Sohn-Rethel’s genetic approach of being nothing more than idealism in the guise of the ultimate materialist critique. Against Horkheimer’s accusations, this article aims to show Sohn-Rethel’s hidden influence on the Dialektik der Aufklärung and more specifically that his reflections help understand the critique of patriarchy. Although Sohn-Rethel is not mentioned, its extension of the materialist and genetic method to the categories of understanding supports the criticism of modern rationality, according to which it is identified with the emergence of male subjectivity.